Перспективи використання похідних хінолін-бурштинової кислоти в технології вегетативного розмноження садових форм Thuja occidentalis L. та Platycladus orientalis (L.) Franco. - Кобець, О. В.; Бредіхіна, Ю. Л.; Завгородній, М. П. (Scientific Bulletin of UNFU, 2022)
It is known that ornamental varieties of Thuja occidentalis L. and Platycladus orientalis (L.) Franco are widely used in landscaping. The lack and high cost of planting material of these varieties encourages Ukrainian horticultural material producers to look for ways to accelerate their propagation. A promising path is a search for new effective and environmentally friendly stimulants of rooting. It was found that disodium salt of 2-(quinolin-4-ylthio) succinic acid (DSQSA) can be considered such a substance with potential growth regulator properties. The experiments were conducted in the horticulture laboratory of the Khortytsia National Training and Rehabilitation Academy in 2018-2020. The authors evaluated the effect of aqueous solutions of the disodium salt of 2-(quinolin-4-ylthio) succinic acid (DNCB) in the concentrations of 10, 25 and 50 mg/l on the rooting and development of green cuttings of Thuja occidentalis "Danica", "Columna", "Globosa"; Platycladus orientalis "Morgan", "Aurea nana", "Pyramidalis" in comparison with the control group where the plants did not receive treatment and their rooting was with "Kornevin" (4-(indol-3-yl) butyric acid). Mother plants are 10-15 years old. Green cuttings were rooted according to the usual technology. In the control group, cuttings were planted for rooting without special preparation. The additional control group comprised cuttings, previously treated with "Kornevin" powder. Before planting, the experimental cuttings had their basal parts immersed for 12 hours in DSQSA solution in the concentrations of 10, 25, 50 mg/l. The experiment was repeated three times, 30 cuttings each. Lowland peat with perlite (1:1) was used as a substrate for rooting. Cuttings were rooted in the greenhouse made of film. At the end of September, the survival of cuttings, as well as the number and length of roots were counted. Rooted cuttings were planted in the open ground for growing. Overwintering plants were counted next years spring. Consequently, the most effective DSQSA concentration was 50 mg/l for rooting most varieties, and 10 mg/l for "Columna" variety. It was found that improving the quality of the root system provided a more successful (10-20 %) rooted cuttings overwintering.